Multiphase high-entropy alloy and preparation method and application thereof
By developing the multiphase high-entropy alloy CoCuMnAlLaCr, the synergistic effect between the high entropy structure and metals, the rapid and efficient activation of PMS and the oxidation-coagulation removal of organic pollutants was achieved, which solved the problems of high energy consumption and insufficient catalyst stability in the prior art, and achieved efficient and low energy consumption pollutant removal effect.
Patent Information
- Application Number
- CN202510020181.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-07
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-07
AI Technical Summary
The prior art has problems of high energy consumption and insufficient catalyst stability when activating persulfate (PMS), making it difficult to achieve efficient activation and low energy consumption at the same time, and it is difficult to take into account both catalytic activity and stability of single metal or bimetallic materials.
A multiphase high-entropy alloy CoCuMnAlLaCr is developed to achieve rapid and efficient activation of PMS by adjusting its elemental composition and phase structure, utilizing the synergistic effect between high-entropy structure and metal, and oxidation-coagulation removal of organic pollutants is carried out by generating MnO2 flocs.
The effect of efficiently activate PMS and remove organic pollutants under normal temperature and pressure conditions is achieved, and the catalyst addition concentration and actual total metal addition concentration are reduced, and the metal ions and small molecule organic by-products are simultaneously recovered, solving the catalyst overflow problem.
Smart Images

Figure CN119824290A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalyst efficient activation of PMS to remove organic pollutants, and in particular relates to a multiphase high entropy alloy and a preparation method and application thereof. Background Art
[0002] Many emerging pollutants are toxic, persistent and non-biodegradable, such as pharmaceuticals and personal care products (PPCPs), endocrine disrupting chemicals (EDCs), per- and polyfluoroalkyl substances (PFAs) and other stubborn organic compounds. However, it is often difficult to effectively remove these emerging pollutants through traditional treatment techniques such as precipitation, activated carbon adsorption, biodegradation, etc. Therefore, it is necessary to develop new technologies to degrade the new difficult-to-degrade pollutants in the environment. Advanced oxidation technology (AOPs) is a promising technology that destroys the chemical structure of pollutants by producing highly oxidizing free radicals and promotes their conversion and mineralization into harmless substances. Peroxymonosulfate (PMS) has attracted much attention due to its superior oxidizing ability. Its chemical formula is HSO5 - , usually in the form of sodium salt (NaHSO5) or potassium salt (KHSO5). It can release sulfate radicals (SO4 - ·), hydroxyl radical (·OH) and other strongly oxidizing free radicals, and rapidly degrade pollutants in water through oxidation reactions. As an emerging environmental governance technology, activated PMS has a wide range of application potentials because it can generate sulfate radicals with high redox potential (2.5-3.1V) and most of its byproducts are pollution-free sulfates. By studying different activation pathways, its removal efficiency of pollutants can be greatly improved.
[0003] The methods that can directly activate peroxymonosulfate mainly include thermal activation, alkali activation, radiation activation, transition metal activation, carbon-based material activation, etc. Among them, transition metal activation can be further divided into homogeneous activation and heterogeneous activation. Although homogeneous activation generally has a high activation efficiency, it is difficult to recycle and has a potential risk of secondary pollution, so its practical value is limited; and through in-depth research on the structure of metal materials, single-atom catalysts, metal-organic frameworks, metal oxides, layered double hydroxides (LDHs) and other transition metal catalysts have been developed, which effectively improve the activation efficiency of heterogeneous catalysis. However, due to the antagonistic effect between the catalytic activity and stability of the catalyst, it is difficult to design single metal or bimetallic materials to show satisfactory performance in two dimensions at the same time.
[0004] High-entropy alloys (HEAs) are a new type of alloy material, usually composed of five or more main elements in approximately the same atomic ratio. The uniqueness of these alloys is that they have a higher entropy value, which makes them more stable when forming a solid solution. At the same time, due to the diversity of their components, they present a unique cocktail effect and a synergistic effect between different elements, which provides more possible paths and unexpected effects for the catalytic process. At present, high-entropy alloys are rarely used in the field of PMS activation. From the perspective of the constituent elements of high-entropy alloys and the different alloy structures themselves affected by the constituent elements, high-entropy alloys have a very large adjustment space and development potential to achieve efficient PMS activation.
[0005] From the perspective of PMS activation, the first problem is the energy consumption problem: thermal activation, radiation activation, photocatalysis, electrocatalysis and ultrasonic catalysis can all effectively activate PMS without considering energy consumption, but this requires very high external energy input and is difficult to put into actual production; the second problem is that the most important thing for PMS activation is to balance the relationship between activation effect and catalyst stability (that is, to prevent secondary metal pollution). The aforementioned single-atom catalysts, metal-organic frameworks, metal oxides, layered double hydroxides and other material structures are limited to a relatively single metal atom composition, or have limited activation ability, limited free radical generation ability, and cannot quickly and effectively degrade target pollutants, or have strong activity but metal overflow cannot be ignored. In summary, for the development of high-entropy alloys, their application in the field of PMS activation is currently limited. At the same time, some existing high-entropy alloy activation PMS schemes are limited to a single phase structure, which can have certain activity and stability, but in the absence of energy input, the overflow of metal ions can be controlled within a certain range, but it cannot be reduced.
[0006] Therefore, there is an urgent need to provide a multiphase high entropy alloy (CoCuMnAlLaCr) and a preparation method thereof that can be used to quickly and efficiently activate persulfate (PMS) and simultaneously produce MnO2 for coagulation and removal of organic pollutants. Summary of the invention
[0007] In view of the above technical problems, the present invention proposes a multiphase high entropy alloy and a preparation method and application thereof.
[0008] To achieve the above object, the present invention provides the following technical solutions:
[0009] One of the technical solutions of the present invention:
[0010] A multiphase high entropy alloy, the metal atomic composition of which includes five or more of Co, Cu, Mn, Al, La or Cr;
[0011] The atomic ratio in the multiphase high entropy alloy is equimolar.
[0012] Preferably, the metal atomic composition of the multiphase high entropy alloy includes: CoCuMnAlLaCr, CuMnAlLaCr, CoCuMnAlCr, CoCuAlLaCr, CoCuMnAlLa or CoCuMnLaCr.
[0013] Furthermore, the metal atomic composition of the multiphase high entropy alloy is CoCuMnAlLaCr.
[0014] Beneficial effects: The present invention utilizes the high entropy structure to adjust the elemental composition of the high entropy alloy and finds a suitable metal combination. First, the Cu element is determined as the basis for forming the FCC structure; Cr and La elements are added to the composition to enrich the phase composition of the material. Cr, as the most stable element in the material, has zero overflow during the reaction process and significantly improves the overall catalytic ability; Co element is introduced to provide active sites as the most effective element for activating PMS; in addition, the present invention also adds Mn element to the high entropy alloy composition and utilizes the reaction of Mn and PMS to generate MnO2 flocculants. In the process of activating PMS, organic pollutants are degraded by oxidation, and small molecular organic matter that is not completely mineralized and a small amount of metal ions overflowed during the reaction are removed by coagulation.
[0015] Preferably, the phase structure of the multiphase high entropy alloy includes: an FCC phase structure and an R-3c phase structure.
[0016] The second technical solution of the present invention:
[0017] The method for preparing the multiphase high entropy alloy comprises the following steps:
[0018] A hydrated nitrate having the above metal atomic composition and ratio is added to a solvent to prepare a precursor solution;
[0019] The precursor solution is pyrolyzed, dried, ground and calcined in sequence to finally prepare the multiphase high entropy alloy.
[0020] Preferably, the solvent is a synthetic solvent, including citric acid and anhydrous ethanol, and the dosage ratio of the two is: citric acid: anhydrous ethanol = 4.18 mmol: 50 mL.
[0021] Beneficial effects: The citric acid in the synthetic solvent acts as a chelating agent in the prepared precursor solution to form a stable complex with the metal ions, which helps to maintain the uniform dispersion of the metal ions; the pH value is adjusted to prevent the metal ions from being hydrolyzed or precipitated in the solution; during the calcination process, the citric acid acts as a carbon source to reduce the metal and reduce the formation of metal oxides; and the gas generated during the thermal decomposition of the citric acid helps to produce gas phase protection during the sintering process, prevent particle agglomeration, form a more uniform particle distribution, and simultaneously introduce micropores or pore structures.
[0022] Preferably, the molar ratio of the citric acid to each (metal) atom is 10:1.
[0023] Preferably, the conditions during the pyrolysis process are: direct pyrolysis at a temperature of 90° C. in a water bath for 1 hour; and / or
[0024] The conditions in the drying process are: drying in an oven at 80° C. for 2 hours; and / or
[0025] The conditions during the calcination process are: calcination at 800-1100° C. for 3 hours in an argon atmosphere.
[0026] Beneficial effects: The present invention synthesizes a hexavalent high-entropy alloy with optimal performance by adjusting the synthesis process, changing the ratio of the synthesis solvent, the water bath temperature, the oxygen and temperature during metal firing (calcination) and other conditions.
[0027] The third technical solution of the present invention:
[0028] The multiphase high entropy alloy is used in the field of rapid and efficient activation of persulfate (PMS) and simultaneous production of MnO2 for coagulation and removal of organic pollutants.
[0029] Beneficial effects: The present invention discloses a multiphase high entropy alloy (CoCuMnAlLaCr) that can be used to quickly and efficiently activate persulfate (PMS) and simultaneously produce MnO2 for coagulation to remove organic pollutants. The principle involved is: by utilizing the four significant core effects of high entropy alloys: lattice distortion effect, high entropy effect, hysteresis diffusion effect, and cocktail effect, the constituent elements and synthesis process of the high entropy alloy are adjusted, and a new multiphase high entropy alloy is designed. On the one hand, the lattice distortion effect is utilized to increase the specific surface area and reaction active sites of the catalyst, thereby improving the catalytic efficiency. The pollutant atrazine is quickly degraded within 2 minutes after the addition of PMS (degradation rate>95%). On the other hand, the high entropy effect is used to achieve stability in the reaction process. At the same time, the cocktail effect is used to design an oxidation-coagulation integrated degradation and removal system. The generated MnO2 flocs are precipitated to remove atrazine and its degradation intermediates. The final total organic carbon (TOC) removal rate of the pollutant solution reaches 75%. The technical effect of precipitating a small amount of overflowed metal ions with coagulation provides a solution for removing a small amount of overflowed metal ions and a part of incompletely mineralized substances in the advanced oxidation process under normal temperature and pressure conditions, and solves the problem of evaluating the effect of the high entropy alloy CoCuMnAlLaCr in activating PMS and degrading and removing organic pollutants.
[0030] Preferably, the organic pollutant is atrazine, whose chemical name is 2-chloro-4-ethylamino-6-isopropylamino-1,3,5-triazine, an organic compound with a chemical formula of C8H 14 C l N5.
[0031] Preferably, the process of removing organic pollutants is:
[0032] Adding the multiphase high entropy alloy into a solution containing organic pollutants, performing ultrasonic and stirring treatment, and obtaining a mixed solution;
[0033] Potassium persulfate (PMS) solution was added to the mixed solution, stirred and filtered.
[0034] Preferably, the added amount of the multiphase high entropy alloy is 0.0167 to 0.0333 g / L.
[0035] Compared with the prior art, the present invention has the following advantages and technical effects:
[0036] 1. The present invention provides a new high entropy alloy composition (CoCuMnAlLaCr);
[0037] 2. The present invention provides a new perspective (multiphase composition) on high entropy alloy series materials in the field of activated persulfate;
[0038] 3. The present invention provides a catalyst (SO4 - ·,·OH,O2· - );
[0039] 4. The present invention utilizes the high entropy structure of high entropy alloy and the synergistic effect between metals to achieve ultra-low catalyst addition concentration (0.0167 g / L) and actual total metal addition concentration (<0.006 g / L);
[0040] 5. The present invention utilizes the cocktail effect and multi-component characteristics of high entropy alloys to create an oxidation-coagulation system for removing organic matter, and simultaneously recovers metal ions and small molecular organic by-products, providing a new solution to the overflow problem of heterogeneous catalytic metals. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0042] Figure 1 This is a comparison chart of the catalytic removal effects of the multiphase high entropy alloys prepared in Examples 1-7 of the present invention and the mixed reagent prepared in Comparative Example 1 on ATZ;
[0043] Figure 2 This is a comparison chart of the removal effect of 0-1.2 mM PMS on 10 ppm ATZ by the high entropy alloy activated by Example 1 of the present invention;
[0044] Figure 3 This is a comparison chart of the catalytic removal effect of ATZ on the multiphase high entropy alloys prepared in Example 1 and Examples 8-12 (different firing temperatures) of the present invention;
[0045] Figure 4 In the effect example, the effect of different catalyst (six-element high entropy alloy prepared in Example 1) dosage on ATZ removal effect under 0.6mMPMS;
[0046] Figure 5 X-ray diffraction patterns of multiphase high entropy alloys (CoCuMnAlLaCr) prepared in Examples 1 and 8-12 of the present invention;
[0047] Figure 6 The infrared spectra of the multiphase high entropy alloy (CoCuMnAlLaCr) prepared in Example 1 of the present invention before and after the reaction, and the infrared spectra of the flocs generated in the system after the reaction in Comparative Example 1;
[0048] Figure 7This is the XPS image of the multiphase high entropy alloy (CoCuMnAlLaCr) prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0049] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0050] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0051] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0052] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0053] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0054] A preparation method of a multiphase high entropy alloy (CoCuMnAlLaCr) that can be used to quickly and efficiently activate persulfate (PMS) and simultaneously produce MnO2 for coagulation and removal of organic pollutants, comprising the following steps:
[0055] (1) Weigh the raw materials: citric acid (CA, C6H8O7·H2O), anhydrous ethanol, Co(NO3)2·6H2O (0.418 mmol), Al(NO3)3·9H2O (0.418 mmol), Mn(NO3)2·4H2O (0.418 mmol), Cr(NO3)3·9H2O (0.418 mmol), La(NO3)3·6H2O (0.418 mmol), Cu(NO3)2·3H2O (0.418 mmol);
[0056] (2) Preparation steps:
[0057] First, 4.18 mmol of citric acid monohydrate (CA, C6H8O7·H2O) was added to 50 mL of anhydrous ethanol and stirred for 10 min to form a colorless and transparent solution;
[0058] Then, equimolar amounts of cobalt nitrate hexahydrate (Co(NO3)2·6H2O, 0.418 mmol), aluminum nitrate nonahydrate (Al(NO3)3·9H2O, 0.418 mmol), manganese nitrate tetrahydrate (Mn(NO3)2·4H2O, 0.418 mmol), chromium nitrate nonahydrate (Cr(NO3)3·9H2O, 0.418 mmol), lanthanum nitrate hexahydrate (La(NO3)3·6H2O, 0.418 mmol) and copper nitrate trihydrate (Cu(NO3)2·3H2O, 0.418 mmol) were added to the above solution in sequence, and after 1 hour of magnetic stirring, a clear and deep purple precursor solution was obtained;
[0059] (3) The precursor solution was placed in a water bath and directly pyrolyzed at 90°C for 1 hour with slow stirring; thereafter, the monomer was allowed to stand at room temperature for 1 hour and then dried in an oven at 80°C for 2 hours; the evaporated crystals were then transferred to a mortar and carefully ground to obtain a light gray powder; finally, the light gray powder was calcined at 900°C for 3 hours in an argon atmosphere to obtain CoCuMnAlLaCr.
[0060] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.
[0061] The raw materials used in the present invention are all purchased from the market.
[0062] The technical solution of the present invention is further illustrated by the following embodiments.
[0063] Example 1
[0064] Preparation process of a multiphase high entropy alloy (CoCuMnAlLaCr):
[0065] (1) Select raw materials: citric acid (CA, C6H8O7·H2O), anhydrous ethanol, Co(NO3)2·6H2O (0.418 mmol), Al(NO3)3·9H2O (0.418 mmol), Mn(NO3)2·4H2O (0.418 mmol), Cr(NO3)3·9H2O (0.418 mmol), La(NO3)3·6H2O (0.418 mmol), Cu(NO3)2·3H2O (0.418 mmol)
[0066] (2) Preparation method:
[0067] First, 4.18 mmol of citric acid monohydrate (CA, C6H8O7·H2O) was added to 50 mL of anhydrous ethanol and stirred for 10 min to form a colorless and transparent solution;
[0068] Then, equimolar amounts of cobalt nitrate hexahydrate (Co(NO3)2·6H2O, 0.418 mmol), aluminum nitrate nonahydrate (Al(NO3)3·9H2O, 0.418 mmol), manganese nitrate tetrahydrate (Mn(NO3)2·4H2O, 0.418 mmol), chromium nitrate nonahydrate (Cr(NO3)3·9H2O, 0.418 mmol), lanthanum nitrate hexahydrate (La(NO3)3·6H2O, 0.418 mmol) and copper nitrate trihydrate (Cu(NO3)2·3H2O, 0.418 mmol) were added to the above solution in sequence. After 1 hour of magnetic stirring, a clear and dark purple precursor solution was obtained;
[0069] Subsequently, the precursor solution was placed in a water bath and directly pyrolyzed at 90 ° C for 1 hour with slow stirring. After that, it was allowed to stand at room temperature for 1 hour and then dried in an oven at 80 ° C for 2 hours. The evaporated crystals were then transferred to a mortar and carefully ground to obtain a light gray powder. Finally, the light gray powder was calcined at 900 ° C for 3 hours under an argon atmosphere to obtain CoCuMnAlLaCr.
[0070] Example 2
[0071] A preparation process of a high entropy alloy (CoMnAlLaCr),
[0072] The difference from Example 1 is that the raw material copper nitrate trihydrate is not added, and the amounts of other raw materials and the preparation process are the same as in Example 1.
[0073] Example 3
[0074] A preparation process of a high entropy alloy (CoCuMnAlCr),
[0075] The difference from Example 1 is that the raw material lanthanum nitrate hexahydrate is not added, and the amounts of other raw materials and the preparation process are the same as in Example 1.
[0076] Example 4
[0077] Preparation process of a high entropy alloy (CoCuMnAlLa),
[0078] The difference from Example 1 is that the raw material chromium nitrate nonahydrate is not added, and the amounts of other raw materials and the preparation process are the same as in Example 1.
[0079] Example 5
[0080] Preparation process of a high entropy alloy (CoCuMnLaCr),
[0081] The difference from Example 1 is that the raw material aluminum nitrate nonahydrate is not added, and the amounts of other raw materials and the preparation process are the same as in Example 1.
[0082] Example 6
[0083] Preparation process of a high entropy alloy (CuMnAlLaCr),
[0084] The difference from Example 1 is that the raw material cobalt nitrate hexahydrate is not added, and the amounts of other raw materials and the preparation process are the same as in Example 1.
[0085] Example 7
[0086] A preparation process of a high entropy alloy (CoCuAlLaCr),
[0087] The difference from Example 1 is that the raw material manganese nitrate tetrahydrate is not added, and the amounts of other raw materials and the preparation process are the same as in Example 1.
[0088] Example 8
[0089] A preparation process of a high entropy alloy (CoCuMnAlLaCr),
[0090] The difference from Example 1 is that the calcination temperature is 600° C. The amounts of other raw materials and the preparation process are the same as in Example 1.
[0091] Example 9
[0092] A preparation process of a high entropy alloy (CoCuMnAlLaCr),
[0093] The difference from Example 1 is that the calcination temperature is 700° C. The other raw material amounts and preparation process are the same as in Example 1.
[0094] Example 10
[0095] A preparation process of a high entropy alloy (CoCuMnAlLaCr),
[0096] The difference from Example 1 is that the calcination temperature is 800° C. The other raw material amounts and preparation process are the same as in Example 1.
[0097] Embodiment 11
[0098] A preparation process of a multiphase high entropy alloy (CoCuMnAlLaCr),
[0099] The difference from Example 1 is that the calcination temperature is 1000° C. The other raw material amounts and preparation process are the same as in Example 1.
[0100] Example 12
[0101] A preparation process of a multiphase high entropy alloy (CoCuMnAlLaCr),
[0102] The difference from Example 1 is that the calcination temperature is 1100° C. The other raw material amounts and preparation process are the same as in Example 1.
[0103] Comparative Example 1
[0104] Reagents: Co(NO3)2·6H2O (0.418mmol), Al(NO3)3·9H2O (0.418mmol), Mn(NO3)2·4H2O (0.418mmol), Cr(NO3)3·9H2O (0.418mmol), Cu(NO3)2·3H2O (0.418mmol).
[0105] Preparation method: Simply mix the above reagents and record them as homogeneous.
[0106] Effect verification:
[0107] The high entropy alloy material prepared above was added into a 10 ppm ATZ (atrazine) solution to verify the catalytic effect of the high entropy alloy.
[0108] Four 60 mL 10 ppm atrazine solutions were prepared, and 1 mg / 2 mg / 6 mg / 10 mg of the CoCuMnAlLaCr prepared in Example 1 were added to the solution for ultrasonication for 5 min, followed by stirring for 25 min, and then 0.3 mL of 120 mM PMS solution was added. Stirring was continued, and 1 mL of sample was taken at regular time intervals and filtered through a 0.22 μm filter membrane and collected into a brown liquid vial. The atrazine concentration was analyzed by HPLC.
[0109] A blank sample was set up without adding any catalyst. 0.3 mL of 120 mM PMS was directly added to 60 mL of 10 ppm atrazine solution. Stirring was continued. Samples were taken at regular time intervals, filtered, and atrazine concentration was analyzed using HPLC.
[0110] A comparative sample was set up. The catalysts prepared in Examples 2-7 and Comparative Example 1 were respectively added to 7 portions of 60 mL of 10 ppm atrazine solution. After adding the catalysts according to the same metal molar concentration as in Example 1, the mixture was ultrasonicated for 5 minutes. Then, 0.3 mL of 120 mM PMS solution was added after stirring for 25 minutes. The mixture was continuously stirred. Samples were taken at regular time intervals, filtered, and the atrazine concentration was analyzed using HPLC.
[0111] A comparative sample was set up. 1 mg of the catalyst prepared in Example 1 was added to 6 portions of 60 mL of 10 ppm atrazine solution, respectively. The mixture was ultrasonicated for 5 min, and then stirred for 25 min before adding 0 mL, 0.15 mL, 0.2 mL, 0.3 mL, 0.45 mL, and 0.6 mL of 120 mM PMS solution, respectively. The mixture was stirred continuously, and samples were taken at regular time intervals, filtered, and the atrazine concentration was analyzed using HPLC.
[0112] A comparative sample was set up. 1 mg of the catalyst prepared in Examples 8-12 was added to 5 portions of 60 mL of 10 ppm atrazine solution respectively. The mixture was ultrasonicated for 5 min, and then stirred for 25 min. 0.3 mL of 120 mM PMS solution was added. The mixture was stirred continuously. Samples were taken at regular time intervals, filtered, and the atrazine concentration was analyzed using HPLC.
[0113] Figure 1 A comparison chart of the degradation and removal effects of 0.6 mM PMS on 10 ppm ATZ (the pH of the original ATZ solution is 7, i.e., the pH of the ATZ solution before adding catalyst and PMS, the same below) activated by the multiphase high entropy alloys (1 mg) prepared in Examples 1-7 of the present invention and the mixed reagent (1 mg) prepared in Comparative Example 1; it can be seen from the figure that the multiphase high entropy alloy prepared in Example 1 of the present invention has the best PMS activation effect, and the degradation rate of ATZ reaches more than 95% within 2 minutes after the addition of PMS.
[0114] Figure 2 This is a comparison chart of the removal effect of 10 ppm ATZ (the pH of the original ATZ solution is 7) activated by 0-1.2 mM PMS on the high entropy alloy (1 mg) prepared in Example 1 of the present invention. It can be seen from the figure that the PMS concentration is the most important factor dominating the degradation effect. 1 mg of the multiphase high entropy alloy prepared in Example 1 of the present invention has sufficient reaction sites to provide higher concentrations of PMS to achieve 100% ATZ degradation within 2 minutes.
[0115] Figure 3 This is a comparison chart of the removal effect of 0.6 mM PMS activated by the high entropy alloy (1 mg) prepared in Example 1 and Examples 8-12 (different firing temperatures) of the present invention on 10 ppm ATZ (the pH of the original ATZ solution is 7); it can be seen from the figure that within different firing temperature ranges, the multiphase high entropy alloy prepared at a calcination temperature of 900° C. adopted in Example 1 of the present invention has an excellent removal effect on organic pollutants, and the removal rate can reach more than 95% within 2 minutes after adding PMS.
[0116] Figure 4 In the effect example, different catalyst (Example 1) dosages affect the removal of ATZ (the pH of the original ATZ solution is 7) under 0.6 mM PMS; it can be seen from the figure that at a dosage of 1 mg, the multiphase high entropy alloy prepared by Example 1 has the best ATZ removal effect, and in terms of dosage, it saves costs.
[0117] Figure 5 This is the X-ray diffraction pattern of the multiphase high entropy alloy (CoCuMnAlLaCr) prepared in Example 1 of the present invention; it can be seen from the figure that under the conditions of heating at 600°C, 700°C and 800°C, the high entropy alloy CoCuMnAlLaCr mainly presents an FCC spatial structure, and when the heating temperature rises to 900°C, the R-3c phase structure grows on the basis of the FCC phase structure and stably coexists with the FCC phase structure.
[0118] Figure 6 The infrared spectra of the multiphase high entropy alloy (CoCuMnAlLaCr) prepared in Example 1 of the present invention before and after the reaction, and the infrared spectrum of the flocs generated in the system after the reaction in Comparative Example 1; it can be seen from the figure that the high entropy alloy CoCuMnAlLaCr material after the degradation reaction basically retains the characteristic peaks of the material before the reaction, which illustrates the stability of the material from a structural perspective; the material after the reaction under the conditions of neutral (pH=7) and acidic (pH=3) original ATZ solution presents the same characteristic peaks as the flocs in Comparative Example 1, indicating that the oxidation-coagulation system is successfully established under neutral and acidic conditions, and the intermediate products of ATZ degradation are effectively combined.
[0119] Figure 7 This is an XPS image of the multiphase high entropy alloy (CoCuMnAlLaCr) prepared in Example 1 of the present invention; it can be seen from the figure that the six metal elements are successfully loaded on the carbon material, and at the same time, in the material, the six metal elements exist in high-valence states, among which Mn, Co, and Cu have multiple valence states.
[0120] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A multiphase high entropy alloy, characterized in that: The metal atomic composition includes five or more of Co, Cu, Mn, Al, La or Cr; The atomic ratio in the multiphase high entropy alloy is equimolar.
2. A multiphase high entropy alloy according to claim 1, characterized in that: The metal atomic composition of the multiphase high entropy alloy includes: CoCuMnAlLaCr, CuMnAlLaCr, CoCuMnAlCr, CoCuAlLaCr, CoCuMnAlLa or CoCuMnLaCr.
3. A multiphase high entropy alloy according to claim 2, characterized in that: The metal atomic composition of the multiphase high entropy alloy is CoCuMnAlLaCr.
4. A method for preparing a multiphase high entropy alloy, characterized in that: The following steps are involved: A hydrated nitrate having the metal atomic composition and ratio according to any one of claims 1 to 3 is added to a solvent to prepare a precursor solution; The precursor solution is pyrolyzed, dried, ground and calcined in sequence to finally prepare the multiphase high entropy alloy.
5. The method for preparing a multiphase high entropy alloy according to claim 4, characterized in that: The solvent is a mixed solution of citric acid and anhydrous ethanol; Wherein, the hydrated nitrate of each metal atom: citric acid: anhydrous ethanol = 0.418 mmol: 4.18 mmol: 50 mL.
6. The method for preparing a multiphase high entropy alloy according to claim 4, characterized in that: The conditions during the pyrolysis process are: pyrolysis at 90° C. in a water bath for 1 hour; and / or The conditions in the drying process are: drying at 80° C. for 2 hours; and / or The conditions during the calcination process are: calcination at 800-1100° C. for 3 hours in an argon atmosphere.
7. Application of the multiphase high entropy alloy according to any one of claims 1 to 3 in the field of rapid and efficient activation of persulfate and simultaneous production of MnO2 for coagulation and removal of organic pollutants, characterized in that: The multiphase high entropy alloy serves as a catalyst.
8. The use according to claim 7, characterized in that: The organic pollutant is 2-chloro-4-ethylamino-6-isopropylamino-1,3,5-triazine.
9. The use according to claim 7, characterized in that: The process of removing organic pollutants is: Adding the multiphase high entropy alloy into a solution containing organic pollutants, performing ultrasonic and stirring treatment, and obtaining a mixed solution; Add potassium persulfate solution to the mixed solution, stir and filter.
10. The use according to claim 9, characterized in that: The addition amount of the multiphase high entropy alloy is 0.0167-0.0333 g / L.
Citation Information
Patent Citations
High-entropy ceramic-high-entropy alloy gradient material and preparation method thereof
CN114606407A
Preparation method of high-entropy alloy composite wave-absorbing material
CN118406925A
Manufacture of hydrogen storage alloy for alkaline storage battery
JP2001023628A
Method for processing ingot and apparatus for processing ingot
KR1020220167223A